RENEWABLE ENERGY POTENTIAL OF SUGARCANE WASTE BIOMASS: A REVIEW - Shahidul, Islam; Shahnur, Begum; Baini, R. (2021)
Traditionally a major percentage of sugarcane waste biomass (SCWB) has been used in various activities. Current practice in the burning of this waste biomass has identified as a poor thermal efficient process, a potential barrier to sugar industries for the achieving of economic sustainability, and indeed a threat to the environment. This study has conducted to reveal advanced technology that is used by sugar mills for the converting of SCWB into energy at a higher thermal efficiency. The data disclosed in this paper have collected from the published papers and reports. A total of sixty research papers and reports on SCWB have reviewed for the collecting of required information, which were mostly published in the years from 2000 to 2021. A major percentage of sugarcane bagasse and trash (SCBT) have been burned conventionally in the atmospheric air, and it becomes a potential source of carbon emission (CO2eq). The range of calorific values of SCBT is from 8MJ/kg to 10MJ/k. Gasification with the combined heat and power (CHP) technology or Pyrolysis with CHP technology has been used for the gaining of higher calorific value (energy) of SCBT. The energy potential of SCBT is about 0.44 MWh/(ton SCBT). The report published by International Renewable Energy Agency (IRENA) demonstrated SCBT is an economically and environmentally feasible renewable solid fuel and a replacement of fossil fuel. IRENA also revealed; SCBT solid fuel is able to reduce 600 kgCO2eq/MWh carbon emission. The information documented in this paper on SCBT's energy potential, the technology used to produce energy, and benefits in carbon emission reduction would be a guideline for energy industries, policymakers, and government agencies for the implementing of economic scale renewable energy projects. This study concludes that the work publishes in this paper is novel, and a road map to produce energy from SCBT for the achieving of economic and energy sustainability for sugar industries. K